Connecting Work To Workers’ Social Past: a Dispositional Analysis of Police Work - Pichonnaz, David (The British journal of criminology, 2021)
This article explores the impact of experiences police officers went through before they joined the Force on how they see and perform their job. I propose a new approach to police culture and practices based on a Bourdieu-inspired model of analysis, which includes its subsequent development by Lahire’s ‘dispositional analysis’. The model looks at how dispositions interiorized—particularly through the experience of social mobility and gender socialization—have a great impact on how police officers see and perform their job. The results suggest that divisions within police culture, long acknowledged by criminologists and sociologists, can be explained by the prior socialization of police officers.